Production and reproduction: stealing the health of future generations - Mengeot, Marie-Anne; Vogel, Laurent (Brussels, 2008)
"This booklet sets out to help improve awareness of work-related reproductive hazards. They are a vast and complex mix of varied kinds running from chemicals, through ionizing radiation, vibration, heat, biological agents to stress and more. They also have a wide variety of effects, including male and female infertility, miscarriages, birth defects, impaired child development and others. And they receive scant attention. There is probably no other sphere of health and safety at work in which the available information is so piecemeal and lacking.